Synbiotic supplement for treatment of iron deficiency anaemia in haemodialysis patients: A randomized controlled trial. Issue 4 (14th February 2023) - Kooshki, Akram; Akbarzadeh, Roya; Amin, Bahareh; Tofighiyan, Tahereh; Foroumandi, Elaheh
Abstract: Background: There is evidence that probiotics can increase the availability of iron. The aim of current study was to determine the effects of synbiotic supplementation on the haematological parameters and anaemia in haemodialysis patients. Methods: This study was a randomized, double‐blind, placebo‐controlled trial. Fifty patients were randomly selected from the haemodialysis section of Vaseii Hospital, Sabzevar, Iran. Subjects in the symbiotic and control groups received 2 capsules of synbiotic supplement or placebo, respectively, once a day for 8 weeks. Blood samples were divided into two test tubes in equal volumes. Blood haemoglobin, haematocrit, transferrin saturation, red blood cells (RBCs), and total iron binding capacity (TIBC) were measured with auto‐analyser. Ferritin was determined using Sandwich enzyme‐linked immunosorbent assay (ELISA). Results: Twenty tree patients in each group completed the study. Significant results were recorded in synbiotic groups regarding the concentration of blood haemoglobin, haematocrit, transferrin saturation, the number of RBCs, and serum ferritin compare to placebo group ( P <  .05). At the end of week 8, TIBC significantly decreased in synbiotic than placebo group ( P <  .05). Conclusion: Synbiotic supplementation could be a safe and promising candidate in improving anaemia in CKD patients. Summary at a Glance: This study shows that synbiotic supplement improve hemoglobin, hematocrit, transferrin saturation, the number of RBCs, and serum ferritin compare to placebo group in patients undergoing haemodialysis. This study inform us important information regarding the effects of synbiotic supplementation in this population.